Stabilization of UAV using Delta Sigma Modulator based controller - Vinoth kumar, V; Diwakar, K; Balasubramanian, E (International Journal of Engineering and Technology, 2018)
The design development and control of Unmanned Aerial Vehicles (UAVâ€™s) have stimulated great significance in the automatic control research for the past 2 decades.Â  In specific, Quad rotor systems are a promising platform in the area of Uthe AV research, due to its simple in construction, maintenance, ability to hover, and their vertical takeoff and landing (VTOL) capability. The dynamics and control of quad rotor are highly nonlinear and under actuated so it is considered as a test-rig to verify any new proposed nonlinear control algorithm. Different control algorithms were proposed and implemented to stabilize the UAV attitude, and altitude. Adaptive control and navigation algorithms also implemented in UAV platform to ensure the maneuvering against the internal and external disturbances. The proposed research paper explains the implementation of the developed digital control algorithm Delta-sigma modulatoan r (DSM) based controller for UAV to enhance the robustness.